Symbolic Meaning of the Ornamental Diversity of Cirebon Batik Pegajahan - Komarudin Kudiya; Setiawan Sabana; Agus Sachari (Mudra Jurnal Seni Budaya, 2016)
Cirebon Batik Pegajahan is the result ofthe creative process, feeling, intention, also long thought of people who have expertise in interpreting the condition of people‘s behavior of Cirebon (palace), which was then adapted into a form of art and culture of batik fabric through a process of creativity of the craftsmen. This Batik Pegajahan grows and develops within the community of (palace) Cirebon, including: Kasepuhan Palace, Kanoman, Kacirebonan, and Keprabonan.This study will explain the symbolic narrative contained in Pegajahan Cirebon batik decoration. The discussion is based on the systematic symbolic visual elements of the Pegajahan batik decoration which is based on the teachings ofthe Tarekat Syattariyah attitudes and behavior of (palace) Cirebon society, form of local wisdom that is reﬂected in the symbolic-aesthetic elements.The research used descriptive—analytic method and ethnography, in describing the symbolic narrative found in Batik Pegajahan Cirebon, The results are in the form ofvisual data complete with symbolic narratives in Batik Pegajahan Cirebon, which represents behavior of (palace) Cirebon people significantly; so it can be used as reference for further research in the reconstruction, reproducing, and formulating such ornaments as the basis for designing or guidance for the people of batik (palace) Cirebon in particular.Keywords: Symbolic Narratives, Decoration of Batik Pegajahan and Tarekat Syattariyah